Multiple melt plumes observed at the Breiðamerkurjökull ice face in the upper waters of Jökulsárlón lagoon, Iceland. Issue 74 (14th June 2017) - Brandon, Mark; Hodgkins, Richard; Björnsson, Helgi; Ólafsson, Jón
ABSTRACT: Breiðamerkurjökull flows from the Vatnajökull ice cap and calves into the Jökulsárlón proglacial lagoon. The lagoon is connected to the North Atlantic Ocean through a 6 m deep narrow channel. Four hydrographic surveys in spring 2012, and a 2011 4-month long temperature and salinity time series of lagoon inflow show that the lake has significantly changed since 1976. Warm saline ocean water enters each tidal cycle and descends below the maximum sampled depths. The lagoon has a surface layer of ice melt, freshwater and Atlantic derived water. Beneath 10 m depth an advective/diffusive balance is responsible for determining the temperature and salinity of the lagoon waters down to ~90 m. To maintain the observed hydrographic structure, we calculate an upwelling of deep water of ~0.2 m d −1 . A survey within 30 m of Breiðamerkurjökull showed that the warmest and most saline waters sampled within the lagoon below 10 m depth were adjacent to the glacier face, along with multiple interleaved warm and cold layers. A heat and salt balance model shows that submarine melting along the ice face generates multiple meltwater plumes that are mixed and diluted within 200 m of the ice face.